Parent education and income gradients in children's executive functions at kindergarten entry. (August 2018) - Conway, Anne; Waldfogel, Jane; Wang, Yi
Abstract: A growing body of research has demonstrated associations between socioeconomic status (SES) and children's early executive function (EF). Yet, although theory and research underscore that distinct components of SES, such as parent education and income, make unique contributions to children's outcomes, few studies have examined these in relation to EF abilities on a population level. To address this gap, we examined a large sample (N = 13, 000) of children from the Early Childhood Longitudinal Study, Kindergarten Class of 2010–2011 (ECLS-K: 2011), a nationally-representative study of children entering kindergarten in the United States. Findings showed parent education and income gradients in cognitive flexibility and working memory at kindergarten entry after controlling for numerous child and family demographics. Notably, gaps were largest for parent education. These findings suggest that greater attention is needed to address parent education, in addition to income, disparities in executive function during early childhood. Highlights: We report substantial parent education and income disparities in children's executive functions at kindergarten entry. Gaps based on parent education were particularly large. Findings are based on a nationally representative sample of children entering kindergarten in the United States in 2011.